STRATEGY FOR OPTIMISING THE ROLE OF INTELLIGENCE IN THE EARLY DETECTION AND PREVENTION OF SECURITY THREATS IN DOMESTIC HIGH-RISK AREAS TO SUPPORT THE NATIONAL DEFENCE STRATEGY - Baginta Bangun; Sigit Purwanto; Bangun Pandapotan Hutajulu (CV RIFAINSTITUT, 2026)
This study analyzes the implementation of intelligence roles in the early detection of security disturbances in vulnerable domestic areas, identifies factors influencing their effectiveness, and formulates optimization strategies to strengthen the national defense strategy. A qualitative descriptive-analytical approach was employed. Data were collected through in-depth interviews, observations, document analysis, and Focus Group Discussions (FGDs), and analyzed using the Miles, Huberman, and Saldaña interactive model integrated with SWOT analysis and the Ends–Ways–Means framework. The findings reveal that the intelligence organization possesses significant strengths, including extensive intelligence networks, regulatory support, experienced personnel, and improving interagency coordination. Nevertheless, challenges remain in information system interoperability, unequal digital technology implementation, and limited human resource competencies in digital intelligence analysis. SWOT analysis positions the organization in Quadrant I (Strength–Opportunity), indicating that a growth strategy is the most appropriate approach through the development of an Integrated Digital Intelligence System, an Artificial Intelligence and Big Data-based Early Warning System, enhancement of human resource competencies, strengthened interoperability, and the expansion of community intelligence. The study concludes that optimizing intelligence functions requires integrated digital transformation, stronger cross-sector collaboration, and continuous organizational capacity development to establish an adaptive and accurate early detection system capable of effectively supporting Indonesia's national defense strategy